Characteristics of the biocontrol rhizobacterium Pseudomonas chlororaphis PCL1606 - Tienda Serrano, Sandra; De-Vicente-Moreno, Antonio; Cazorla-López, Francisco Manuel (My University, 2017)
The major disease affecting avocado crops in the Mediterranean area is Rosellinia necatrix, causing the avocado white root rot. The biocontrol rhizobacterium Pseudomonas chlororaphis PCL1606 has been isolated from rhizosphere of healthy avocado trees, growing in an area affected by white root rot. As a main characteristic, PCL1606 showed a strong in vitro antagonism against R. necatrix and other important soil borne pathogens, mainly due to the production of the antimicrobial compound 2- hexyl, 5-propyl resorcinol (HPR), moreover, production of other antifungal compound has been also detected. PCL1606 has the ability to persist and to colonize the avocado roots, where, interacts closely and colonizes the fungal hyphae of R. necatrix, leading to a negative effect to the fungus. Those phenotypes, acting together allowed PCL1606 to display biocontrol activity towards R. necatrix in avocado plants. Interestingly, we have observed that PCL1606 shows no plant growth promoting activities. Finally, the availability of the complete genome sequence of PCL1606 will allow us to identify additional features involved in the biocontrol.
Contribución oral a conferencia.
Keywords: Aguacate - Enfermedades; Rosellinia necatrix, avocado, biological control, antagonism